THE STUDY OF MATERNAL OUTCOME FOLLOWING EARLY AND DELAYED CORD CLAMPING IN BIRTHS ASSOCIATED WITH ANEMIA IN PREGNANCY - singh, lata; Deepika; CHITRA RAGHUNANDAN (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: (The objectives of the study are as follows: 1) To compare the Blood loss in both early cord clamping (ECC) versus delayed cord clamping (DCC) (in the third stage of labor). (2) To compare the third-stage complications following ECC versus of DCC in anemic pregnant females. (3) To compare Maternal hemoglobin and hematocrit at 24 h of delivery in both ECC versus DCC. Methods: This prospective study was carried out in the Department of Obstetrics and Gynaecology in Lady Hardinge Medical College and Associated Hospitals, New Delhi pregnant women. A total of 120 anemic pregnant women between 32 and 40 weeks of gestation admitted in the labour room were enrolled in the study (hemoglobin between 7 and 10.9 g%). Twenty patients were lost to follow-up. Third-stage complications of 46 women who underwent ECC (<60 s) were compared with 54 women who underwent DCC (more than 60 s to <3 min). Maternal hemoglobin and hematocrit at 24 h of delivery were also compared between both groups. Results: The mean blood loss in both the groups was 325±89.287 and 326.85±66.384, comparable statistically with p=0.906. Out of 100 patients enrolled, only two patients had postpartum hemorrhage. Each one belonged to each group (p<0.909). None of the groups had retained placenta showing no statistical significance between two groups (p<1). DCC was not associated with increased risk of third-stage complications whether in cesarean section or vaginal delivery. There were no differences in operative time, post-delivery decrease in hematocrit, rates of postpartum hemorrhage, bleeding complications, maternal blood transfusions, and therapeutic hysterectomy between the two groups. Conclusions: DCC is safe for mother especially in anemic mothers also as it does not increase the mean blood loss and also it has beneficial effect on neonates. No difference in third-stage complications and maternal hemoglobin and hematocrit levels at 24 h in both groups. It should be recommended in routine practice where it is not contraindicated especially in resource-poor settings.